High school teachers' lived experiences of bullying by learners in the Namakgale Circuit, Limpopo Province - Mangena, Madie Collen (My University, 2022)
Background: Bullying has been reported to be on the rise in the world. South Africa is no exception. In recent years bullying has been reported to impact severely, resulting in resignations by teachers from the teaching profession. The researcher looked at the school as the workplace for teachers who experienced bullying. The study was about occupational health and safety for teachers, which is an important public health issue. The employer is obliged to create a conducive workplace for teachers as employees working at schools. Objectives: The objectives of the study were to explore and describe high school teachers’ lived experiences of bullying by learners in Limpopo Province. Methods: The qualitative and descriptive phenomenological method was followed. Due to data saturation, ten teachers participated after being selected through purposive sampling from seven high schools. Research ethics were observed. Data was collected through semi-structured interviews using an interview guide. Interviews were audio-taped and field notes were taken. Voice recordings were transcribed verbatim and analysed using open coding thematic analysis. Findings were confirmed by an independent coder. Results: The findings reveal that bullying is not a new phenomenon in schools in South Africa and globally. Most teachers perceive bullying differently. Some perceive acts of violence amongst learners as bullying. Some interpret noise in the classrooms as bullying, some view overcrowding in the classrooms contributing to bullying. Some perceive substances and drug abuse as causing bullying in schools. Most teachers experience feelings of hopelessness and powerlessness. They are sad, and feel small, embarrassed, intimidated, angry, disappointed etc. Some lack support from school management and governance, and others experience different forms of bullying. Some refrain from their style of teaching as it impacted on their teaching duties. The findings furthermore indicate that bullying affects both males and females but differently. Female teachers were more prone to bullying than male teachers. Conclusion: The outcomes of the study have revealed that bullying is a reality. Teachers are being targeted by learners at schools. They seemed not to understand policies and procedures to intervene when addressing bullying at schools. Interventions were not effective due to lack of knowledge and poor policy implementation. Bullying is not a new concept in the Department of Education. Unions, SGBs and SACE are aware of incidents that happen in schools. The Department of Education should ensure that teachers are protected when rendering their teaching services in schools.
Thesis (MPH.) -- University of Limpopo, 2022
Keywords: Bullying; Experiences; High school; Learner; Teacher; Bullying in schools; High school teachers -- South Africa -- Limpopo